STAB Maitreyawira Alumni's Perception of Buddhist Business Law (Case Study of Alumni of the Buddhist Religious Education Study Program) - Rida Jelita; Hosan; Irawati; Yadi Sutikno; Suryati (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Alumni of the Buddhist Religious Education Study Program (PKB) STAB Maitreyawira are spread across various places, with various jobs, for example, some become Educators/Teachers, religious instructors, civil servants, and self-employed/entrepreneurs, and so on. The focus of this study is to analyze the perception/understanding of PKB Study Program alumni regarding the principles of business law in Buddhist teachings, the application of moral values in business law practices, and the factors that influence them in applying these principles in the world of work. This study aims to analyze the perceptions of PKB Study Program alumni STAB Maitreyawira towards the concept of Buddhist business law and the factors that influence them in applying these principles in the world of work. The research method used is a qualitative approach. The study results show that PKB Study Program alumni STAB Maitreyawira have a positive perception of Buddhist business law and strive to apply it in the world of work. However, various factors influence the implementation of these values. Namely, internal factors include: Psychological Needs, Educational Background, Experience factors, Good looking values (attractive) and Self-confidence, and external factors include: Buddhist Business Law Material during Lectures, Economic Conditions, Technology, and Digital. Therefore, it is necessary to strengthen Buddhist business law in the curriculum and support from the Alumni community in building a business environment based on moral and ethical values